ATRIAL FIBROSIS IS A MORPHOLOGICAL BASIS OF ATRIAL FIBRILLATION - O. M. Drapkina; A. V. Emelyanov (Рациональная фармакотерапия в кардиологии, 2015)
Mechanisms of atrial fibrosis including the role of serotonin in the development of this lesion in patients with atrial fibrillation are presented. New approaches to the treatment of atrial fibrillation aimed at atrial fibrosis reduction are discussed.